Herpes simplex Virus Pneumonitis in an Acute/Subacute Paracoccidioidomycosis Patient With Malabsorption Syndrome. Case-Report and Literature Review - Cavalcante, Ricardo S. [UNESP]; Souza, Bruno S. [UNESP]; Duarte, Iverson X. [UNESP]; Moraes, Marcelo P. T. [UNESP]; Coelho, Kunie I. R. [UNESP]; Griva, Beatriz L. [UNESP]; Pereira, Beatriz A. S. [UNESP]; Calvi, Sueli A. [UNESP]; Betini, Marluci [UNESP]; Mendes, Rinaldo P. [UNESP] (Frontiers, 2021)
Paracoccidioides sp.—Herpes simplex virus (HSV) co-infection was not reported until now and malabsorption syndrome is a rare complication of the acute/subacute form (AF) of paracoccidioidomycosis (PCM), characterized by life-threatening abnormalities, such as fat and protein loss, lymphopenia, ascites, and intense immunosuppression. A 21-year-old woman presented the PCM AF with intense involvement of the abdominal and intestinal lymphoid organs, which leads to the malabsorption syndrome and severe immunosuppression. This patient developed a fatal-disseminated HSV infection associated with the paracoccidioidal disease. This case demonstrates that, in addition to the antigen-specific immunosuppression, some PCM patients can present a generalized cell-mediated immune depression and endogenous infection of latent microorganisms. On the best of our knowledge, this is the first report of an association between PCM and HSV infection.
Keywords: Herpes simplex pneumonitis; herpetic infection and malnutrition; malnutrition; Paracoccidioides brasiliensis; paracoccidioidomycosis; paracoccidioidomycosis-herpetic infection comorbidity